Aktivitas Pemijahan, Perkembangan Awal, dan Pertumbuhan Larva Ikan Pelangi Arfak dalam Kondisi Laboratorium: Studi Pendahuluan untuk Penangkarannya - Emmanuel Manangkalangi; Ida Lapadi; Paskalina Theresia Lefaan; M. Fadjar Rahardjo; Renny K. Hadiaty; Sigid Hariyadi; Charles P. H. Simanjuntak (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Comprehensive information regarding the reproduction, early development, and growth of larvae is very important in the efforts of captive breeding and reintroduction of endangered fish species. One of the species that is starting to be threatened is the Arfak rainbowfish, Melanotaenia arfakensis which is already in the vulnerable category and its information is still relatively limited. Therefore, this study was conducted to describe the spawning activity, early development, and growth of the larvae of this rainbow fish species under laboratory conditions. Experiments on a laboratory scale were carried out in March-September 2017. The fish used came from the Nimbai Stream. A total of three pairs of individual males and females ranging in size from 46.5 to 60.1 mm were selected for treatment. However, only one pair was successfully observed spawning activity completely. Spawning takes place between morning and noon in three spawning periods. In each period, spawning lasts between 8 and 11 days. Between spawning periods takes 14 to 22 days. After fertilization, the eggs are attached with filaments to the spawning substrate and placed at a depth of 7.3-24.3 cm from the surface of the water. One group of eggs spawned consists of 78-116 eggs with a diameter range between 1.05 and 136 mm. The eggs hatch in a period of 4 to 10 days. The body length of the newly hatched larvae ranges from 4.13-4.40 mm and will reach a size of 7.85 mm with a survival rate of 48.1% after 41 days. The results of this study found several advantages from the characteristics of spawning and growth in the early stages that are useful for captive breeding efforts and reintroduction of this rainbowfish to their natural habitat. Thus, its population in the Prafi River system can be maintained.